Clinical-pathogenetic and prognostic value of the nitrotyrosine level in the blood serum of patients with coronavirus disease (COVID-19) with pneumonia - O. V. Riabokon; I. O. Kuliesh; I. F. Bielenichev; Yu. Yu. Riabokon (Zaporozhye State Medical University, 2024)
The aim of the research is to determine the clinical-pathogenetic and prognostic value of nitrotyrosine levels in the blood serum of patients with COVID-19 with pneumonia in the development of oxygen dependence and the risk of fatal outcome. Materials and methods. 123 patients with COVID-19 with pneumonia were examined, who were examined and treated according to the Order of the Ministry of Health of Ukraine dated March 28, 2020 No. 722. Patients were divided into groups: I group - 32 patients with a moderate course without oxygen dependence; II group - 91 patients with a severe course with the presence of oxygen dependence. Patients in the II group were additionally divided into subgroups: II-A subgroup - 45 patients who recovered; II-B subgroup - 46 patients who died. The content of nitrotyrosine (Hycult Biotech, the Netherlands) was determined in the blood serum by the immunoenzymatic method. Statistical data processing was carried out in the program Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. The content of nitrotyrosine in the blood serum of patients with COVID-19 with pneumonia in a severe course with the development of oxygen dependence is higher (p < 0.001) than in patients with a moderate course of the disease without signs of oxygen dependence. The level of its increase has an inverse correlation with the oxygen saturation index (r = -0.53, р < 0.05). When hospitalized for 9.0 [7.0; 12.0] day of the disease, under the condition of nitrotyrosine level >481.97 nmol/ml (AUC = 0.909, p < 0.001), the probability of developing oxygen dependence is significant. And under the conditions of nitrotyrosine level >521.96 nmol/ml during this observation period, the probability of a fatal outcome of the disease is significant (AUC = 0.842, p < 0.001). The established correlations confirm the clinical-pathogenetic role of nitrotyrosative stress in the development of the "cytokine storm" and multiorgan failure. The content of nitrotyrosine correlates with the level of C-reactive protein (r = +0.25, p < 0.05), the ratio of absolute neutrophil count to absolute lymphocyte count (r = +0.26, p < 0.05), alanine aminotransferase activity (r = +0.26, p < 0.05) and glomerular filtration rate (r = -0.27, p < 0.05). The diagnostic value of determining the level of nitrotyrosine in predicting the course of COVID-19 with pneumonia against the background of treatment after 7 days lies in the possibility of predicting the probability of a fatal outcome of the disease. Namely, the preservation of the level of nitrotyrosine >507.98 nmol/ml (AUC = 0.681, p < 0.001) during the specified period of observation indicates a high probability of a fatal outcome of the disease. Conclusions. In patients with COVID-19 with pneumonia, the level of nitrotyrosine elevation in the blood serum depends on the appearance of oxygen dependence and the outcome of the disease. The highest level of nitrotyrosine is in patients with COVID-19 with pneumonia with a severe course, and the degree of increase of this indicator has diagnostic value in predicting the probability of an unfavorable disease course.